Exploring the Physical and Mental Strain of Traditional Farming on Rural Women and the Impact on Youth’s Declining Interest in Agriculture - Bhuyan, Bijoylaxmi; Bhattacharyya, Nandita; Kalita, Mira; Meenakshi, Namburi; Upadhyaya, Eliza (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during May, 2021–April, 2022 at four randomly selected villages located in the radius of 5–7 km from Diphu town in the District of Karbi Anglong, Assam, India to study the physiological strain and discomfort experienced by rural women engaged in myriad activities such as load carrying, hoeing, weeding etc. and household weaving in Traditional farming practices in rural settings. A sample of 100 women was surveyed, and data were analyzed with Rating of Perceived Exertion (RPE) scale. Results showed significant discomfort in body parts such as the lower back, wrists, and legs. Additionally, psychosocial stress and mental health challenges related to the workload were identified, highlighting the hidden strain rural women face. The study suggested to use ergonomically designed farming tools and interventions to alleviate physical strain, as well as psychological support to mitigate stress. Further, the impact of these physical and mental stresses extends beyond the women themselves, discouraged younger generations from pursuing farming as a livelihood. This shift toward seeking alternative employment had worsened rural unemployment and exacerbated the challenges faced by agricultural communities which in turn provided hindrance in sustainable development. Studies of recent time had explored the link between labour intensity with mental health in rural women, indicating the necessity of recognizing the intersection of physical and mental health issues in rural work environments.